CHARACTERIZATION OF POSITIVE DEFINITE FUNCTIONS ON Rs - Ma'un Karimah, Veri
This thesis discusses about the necessary and sufficient conditions for positive definite functions on Rs. These conditions are obtained by using Fourier transformation and measure. In addition, this thesis also discusses about properties of positive definite functions on Rs.